Mathematical Modeling and Study of The Process of The Conversion of The Mellon on Juice and Puree - Samadov O; Dodaev K; Choriev A; Yangiboyev Y (Zien Journals, 2022)
The universal model of process of multiphasic evaporation is received and the software received analytical and experimental models is carried out, optimum parameters are revealed at processing a melon in an offered line
Keywords: line; optimum; parameters; processing